Energy Management System and Control Strategy of Intelligent Connected New Energy Vehicle in Line with the Dual-Carbon Strategy - Jiaqi Tan; Yunyi Zhang; Yanjie Zhao; Fangyang Zhang (Advances in Multimedia)
This thesis studies the development of the energy management system and control strategy of intelligent connected new energy vehicles and discusses the core techniques of the energy management system and control strategy of the vehicles. The energy management control strategy holds the key for the development of the new vehicles. It is designed to use its energy-saving principles and technologies to give full play to the energy-saving potential of the design scheme, thus optimizing the energy efficiency of the entire vehicle while meeting the driving needs of vehicles according to the performance characteristics of key components and the driving conditions of the vehicle. This thesis not only analyzes the V2X standards to be met in the application of ICV technology and briefly describes the CD/CS strategy and Blended strategy of plug-in hybrid vehicles and the energy management control strategy based on rules and optimization but also studies the control and strategy of information management system in practical circumstances.